2017
DOI: 10.28945/3666
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Agile Maturity Model Research

Abstract: Background/Aim/Purpose: A commonly implemented software process improvement framework is the capability maturity model integrated (CMMI). Existing literature indicates higher levels of CMMI maturity could result in a loss of agility due to its organizational focus. To maintain agility, research has focussed attention on agile maturity models. The objective of this paper is to find the common research themes and conclusions in agile maturity model research. Methodology: This research adopts a systematic appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
(49 reference statements)
0
11
0
Order By: Relevance
“…Ramasubbu and Niazi et al stated that currently, software organizations are working on distributed software product development, and thus, the proponents of SPI in an organization must pay attention to process improvement efforts by leveraging the diversity of practices. Kuhrmann et al and Henriques and Tanner provided a systematic mapping study and systematic reviews with the focus on the use of agile methods with the CMMI model. The studies as mentioned above have following limitations.…”
Section: Related Workmentioning
confidence: 99%
“…Ramasubbu and Niazi et al stated that currently, software organizations are working on distributed software product development, and thus, the proponents of SPI in an organization must pay attention to process improvement efforts by leveraging the diversity of practices. Kuhrmann et al and Henriques and Tanner provided a systematic mapping study and systematic reviews with the focus on the use of agile methods with the CMMI model. The studies as mentioned above have following limitations.…”
Section: Related Workmentioning
confidence: 99%
“…In the area of the usability engineering, Lacerda and von Wangenheim conducted an SLR with 15 usability capability/maturity models. SLR studies on supply chain maturity models, KM maturity models, and agile maturity models were performed by Correia et al, Pour et al, and Henriques and Tanner, respectively. Similar to the previous mapping studies, one or more concerns on model validity such as a lack of information on model design/development, insufficient support for model usage/adoption in practice, scarce empirical evidence, and questionable validity and usefulness of the models were mentioned in their study areas of interest.…”
Section: Related Workmentioning
confidence: 99%
“…All of previous mapping studies showed that maturity model publications have been expanding beyond IT sector. On the other hand, they raised concerns of the validity of models; several SLRs showed the status of maturity models in the limited domains such as business process management (BPM) and usability, which would be an echo of the mapping studies. However, to the best of our knowledge, previous studies did not provide the specific names of the maturity models used across domains and those that have been statistically validated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review of Agile maturity models [32] identified that the agile maturity model literature was predominantly divided into two major groups. The first was concerned with the co-existence of agile methods in an environment where CMMi was present [45] and the second related to improving agile implementations without the consideration of other process improvement frameworks.…”
Section: Agile Maturitymentioning
confidence: 99%